Predicting hemorrhagic transformation after large vessel occlusion stroke in the era of mechanical thrombectomy. - Takanori Iwamoto (Public Library of Science (PLoS), 2021)
Serum biomarkers are associated with hemorrhagic transformation and brain edema after cerebral infarction. However, whether serum biomarkers predict hemorrhagic transformation in large vessel occlusion stroke even after mechanical thrombectomy, which has become widely used, remains uncertain. In this prospective study, we enrolled patients with large vessel occlusion stroke in the anterior circulation. We analyzed 91 patients with serum samples obtained on admission. The levels of matrix metalloproteinase-9 (MMP-9), amyloid precursor protein (APP) 770, endothelin-1, S100B, and claudin-5 were measured. We examined the association between serum biomarkers and hemorrhagic transformation within one week. Fifty-four patients underwent mechanical thrombectomy, and 17 patients developed relevant hemorrhagic transformation (rHT, defined as hemorrhagic changes ≥ hemorrhagic infarction type 2). Neither MMP-9 (no rHT: 46 ± 48 vs. rHT: 15 ± 4 ng/mL, P = 0.30), APP770 (80 ± 31 vs. 85 ± 8 ng/mL, P = 0.53), endothelin-1 (7.0 ± 25.7 vs. 2.0 ± 2.1 pg/mL, P = 0.42), S100B (13 ± 42 vs. 12 ± 15 pg/mL, P = 0.97), nor claudin-5 (1.7 ± 2.3 vs. 1.9 ± 1.5 ng/mL, P = 0.68) levels on admission were associated with subsequent rHT. When limited to patients who underwent mechanical thrombectomy, the level of claudin-5 was higher in patients with rHT than in those without (1.2 ± 1.0 vs. 2.1 ± 1.7 ng/mL, P = 0.0181). APP770 levels were marginally higher in patients with a midline shift ≥ 5 mm than in those without (79 ± 29 vs. 97 ± 41 ng/mL, P = 0.084). The predictive role of serum biomarkers has to be reexamined in the mechanical thrombectomy era because some previously reported serum biomarkers may not predict hemorrhagic transformation, whereas the level of APP770 may be useful for predicting brain edema.